‘Is it Genocide or not?’ Some Considerations about the Ethnic Cleansing and Punishment System in Soviet Union (1930s-1950s) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2024)
This study examines Stalin-era ethnic cleansing in the Soviet Union, focusing on the mass repression and deportation of groups such as the Volga Germans and Crimean Tatars. It introduces the debate, supported by specific evidence, about the deliberate oppression of ethnic minorities as part of Stalinist Soviet policy, as legitimised by legal measures. Through actions such as forced relocation, executions and cultural suppression, the analysis explores how Soviet policy aimed to dismantle ethnic identities without outright destruction. It situates these actions within genocide studies, drawing on the theories of Raphael Lemkin and UN definitions. Ultimately, it calls for a nuanced view of ethnic persecution in the USSR, emphasising the legal and historical impact of these localised acts of genocide on the communities affected.
Keywords: Eastern European Studies; Stalinism; History of camps; Genocide Studies; Transitional Justice